Accuracy of vascular invasion reporting in hepatocellular carcinoma before and after implementation of subspecialty surgical pathology sign-out - Aaron R Huber; Raul S Gonzalez; Mark S Orloff; Christopher T Barry; Christa L Whitney-Miller (Wolters Kluwer Medknow Publications, 2017)
Context: Liver cancers (including hepatocellular carcinoma [HCC] and cholangiocarcinoma) are the fifth most common cause of cancer death. The most powerful independent histologic predictor of overall survival after transplantation for HCC is the presence of microscopic vascular invasion (VI). Aims: Given that VI is known to have somewhat high interobserver variability in both HCC and other tumors, we hypothesized that pathologists with special interest and training in liver pathology would be more likely to identify and report VI in HCC than would general surgical pathologists. Settings and Design: We searched our departmental surgical pathology archives for transplant hepatectomies performed for HCC. Subjects and Methods: We identified 143 such cases with available sign-out reports and hematoxylin and eosin-stained slides. Statistical Analysis Used: Kappa results (level of agreement) were calculated. Results: Before surgical pathology subspecialty sign-out (SSSO) implementation, 49 of 88 HCC cases were reported as negative for VI; on rereview, 20 of these had VI. After SSSO implementation, 39 of 55 cases were reported as negative for VI; on our review, 8 of these had VI. Kappa (agreement) between general SO and subspecialty rereview was 0.562 (95% confidence interval [CI] = 0.411-0.714) "weak agreement." Kappa (agreement) between SSSO and rereview by select liver pathologists was 0.693 (95% CI = 0.505-0.880) "moderate agreement." Conclusions: Our study is one of only a few so far that have suggested improved accuracy of certain parameters under SSSO.